RESPIRATION FREQUENCYON A BALI CATTLE ADULT FEMALE AT BALI CATTLE BREEDING CENTERS SOBANGAN VILLAGE, MENGWI, BADUNG - Serang, Priska Mariane; Suartha, I Nyoman; Arjentinia, I Putu Gede Yudhi (Buletin Veteriner Udayana, 2016)
Bali cattle females to be one of the priorities in repairing genetic local cattle because of its superiority in the field of production and reproduction compared to other cattles. This research aims to determine the respiration profile on a bali cattle adult female at Bali cattle breeding centers Sobangan village, Mengwi sub district, Badung regency, which has an average altitude of 350 meters above sea level and rainfall reached around 2029.0 mm. This research used 20 bali cattle adult female age 1.5 years to 4 years. Data collected by examination and observation were performed in the morning, afternoon and evening. The observed parameters are the frequency of respiration. The results obtained by the average frequency of respiration morning of 16.05±0.82 at 25°C ambient temperature, daylight 20.95±0.88 at 32°C ambient temperature, and the afternoon of19.80±1.57 at 29°C ambient temperature. These results indicate that the frequency of respiration in Bali cattle females can be changed according to environmental conditions and other contributing factors.
Keywords: female bali cattle; respiration frequency; Sobangan